KAJIAN TERHADAP TRADISI HUKUM WARIS MASYARAKAT ADAT TENGGER - Farisma Eka Avaria; Farrel Al Hafiz; Indah Novitasari Nasution; Kinanti Putri Purnomo; Mirna Fajar Rahmawati (Jurnal Humaniora & Sosial Sains, 2025)
This study aims to analyze and also find out about the inheritance law in the Tengger tribe, which has a unique inheritance law that is passed down from generation to generation. The method used for this study is by using the literature review method. The results of this study indicate that the Tengger tribe has a bilateral inheritance system by equating boys with girls. For children who look after and care for their parents until they die, they will be given an award in the form of "hung land". If there is a problem or dispute in the distribution of this inheritance, then a deliberation and consensus will be held which will be attended by community leaders and the local village government. The inheritance law carried out in the Tengger tribe has quite striking differences with the national inheritance law, which upholds the values ​​of family, justice, balance, and obedience. Although the Tengger tribe's inheritance law system can be said to be quite different from national law, until now the Tengger tribe still continues to uphold and preserve this ancestral culture.